Spray Serai Anti Nyamuk Anti-Mosquito Spray from Lemongrass as a Mosquito Bite Prevention with Dengue Fever - Farid Setyo; Budi Rahardjo; Bibit Irawan (Universitas Veteran Bangun Nusantara, 2026)
ABSTRACT Vector-borne diseases, particularly mosquitoes like Aedes aegypti, remain a serious public health issue in Indonesia. One environmentally friendly solution is the use of mosquito-repellent plants such as citronella (Cymbopogon nardus), which contains active compounds such as citronellal and geraniol, which have been proven effective as natural repellents. This community service program aims to provide training to residents on how to make mosquito repellent spray from citronella, while also encouraging the potential for home-based businesses based on natural ingredients. The implementation method includes counseling, demonstrations, and hands-on practice in spray making. The results showed that participants experienced an increase in their understanding of dengue fever by 30%, the benefits of citronella by 33%, extraction skills by 55%, spray formulation by 57%, and packaging by 40%. This activity also succeeded in fostering entrepreneurial interest among participants. Thus, this training not only provides a preventive solution to vector-borne diseases but also opens up opportunities for economic growth based on local potential. Keywords: Vector-borne diseases, Citronella-based repellent, Community empowerment